Human cytomegalovirus antiviral drug resistance in hematopoietic stem cell transplantation: current state of the art. (14th March 2016) - Campos, Ana Bela; Ribeiro, Joana; Boutolleau, David; Sousa, Hugo
Summary: Human cytomegalovirus (HCMV) infection is a major cause of morbidity and mortality in allogeneic hematopoietic stem cell transplant recipients. The significant clinical impact of HCMV infection and progression to HCMV disease among allogeneic hematopoietic stem cell transplant recipients has been reduced by prophylactic, preemptive, and curative treatments using ganciclovir, valganciclovir, foscarnet, and cidofovir. Resistance to (val)ganciclovir results from mutations localized in HCMV UL97 gene (encoding the pUL97 phosphotransferase), UL54 gene (encoding the pUL54 DNA polymerase), or both genes, whereas foscarnet and cidofovir resistance results from mutations localized within UL54 gene only. This review is focused on HCMV antiviral drug resistance, including the functions of target genes of antivirals, the mechanisms of antiviral resistance, the different mutations in pUL97 and pUL54 that have been identified in either clinical isolates or laboratory strains, and their impact on HCMV susceptibility to antiviral drugs. It emphasizes the importance of proving that observed genetic changes confer resistance so they can be distinguished from polymorphisms. Because of the emergence of HCMV resistance to currently available drugs, novel drugs are urgently needed for the therapeutic management of HCMV‐resistant infections in hematopoietic stem cell transplant patients. Copyright © 2016 John Wiley & Sons, Ltd.